2001
DOI: 10.1021/ac0102056
|View full text |Cite
|
Sign up to set email alerts
|

Microcalorimetric Studies on the Interaction Mechanism between Proteins and Hydrophobic Solid Surfaces in Hydrophobic Interaction Chromatography:  Effects of Salts, Hydrophobicity of the Sorbent, and Structure of the Protein

Abstract: This study examines the effects of different salts as well as the influence of the relative hydrophobicities of different sorbents on the adsorption processes of proteins in hydrophobic interaction chromatography (HIC). Comparative data acquired by the equilibrium binding analysis and by isothermal titration microcalorimetry (ITC) are presented. In particular, thermodynamic parameters, including the enthalpy changes, related to the interactions between several globular proteins and various Toyopearl 650 M sorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 52 publications
(104 reference statements)
3
57
0
Order By: Relevance
“…For example, the energy for adsorption of a 13-residue peptide on colloidal silica was measured to be about 36 kJ/mol (41); binding of relatively small proteins such as lysozyme (14.3 kDa) or RNase A (13.7 kDa) to different chromatographic solid supports was indicated in the range of 13-34 kJ/mol (42)(43)(44), and the binding energy of a series of proteins to the aluminum salt ranges from about 30 to 40 kJ/mol (45). Assuming E b ϭ 20 kJ/mol and d corresponds to the molecular size of the IFNG molecules (about 4-nm diameter), the two-stage diffusion mechanism can only be significant in our incubation chamber with R c Ϸ 0.35 cm for R of only a few m or even less (the dominating mechanism if R Ͻ (DЈ/D)10 Ϫ4 cm).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the energy for adsorption of a 13-residue peptide on colloidal silica was measured to be about 36 kJ/mol (41); binding of relatively small proteins such as lysozyme (14.3 kDa) or RNase A (13.7 kDa) to different chromatographic solid supports was indicated in the range of 13-34 kJ/mol (42)(43)(44), and the binding energy of a series of proteins to the aluminum salt ranges from about 30 to 40 kJ/mol (45). Assuming E b ϭ 20 kJ/mol and d corresponds to the molecular size of the IFNG molecules (about 4-nm diameter), the two-stage diffusion mechanism can only be significant in our incubation chamber with R c Ϸ 0.35 cm for R of only a few m or even less (the dominating mechanism if R Ͻ (DЈ/D)10 Ϫ4 cm).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the solute affinities on HIC stationary phases were also found to have a linear relationship with the lyotropic series. Lin et al (2000Lin et al ( , 2001Lin et al ( , 2002 studied the effects of salt, ligand hydrophobicity, and protein structure on the interaction between protein and ligand using microcalorimetric measurement. Byun et al (2000) explained the salt effects on peptide binding on a SynChropak column and found that a salting-in parameter and a surface tension parameter could be very useful for peptide binding mechanism study.…”
Section: Introductionmentioning
confidence: 99%
“…11 The similar conclusion was affirmed in adsorption isotherm and chromatographic retention of BSA by Gao et al 12 In a combination with equilibrium binding analysis and isothermal titration microcalorimetry (ITC) measurements, Lin et al found that aromatic stacking contributed to protein adsorption on aromatic-based HIC adsorbents (e.g., Phenyl Sepharose). 13 Besides that, a typical HCIC chromatographic process is also influenced by other factors, such as the composition of the liquid phase, pH, and temperature. 2,11,12 Therefore, a better understanding of the mechanism of protein adsorption on HCIC beads is indispensable for the development and application of HCIC technology.…”
Section: Introductionmentioning
confidence: 99%
“…ITC has been successfully used to acquire thermodynamic data in protein adsorption on various ion exchange and hydrophobic interaction adsorbents. [13][14][15] For this purpose, we synthesized a histamine-Sepharose (HA-S) gel with higher ligand density than the histamine-ligand chromatography media reported previously. [16][17][18] Lysozyme was chosen for adsorption onto HA-S because it has been used extensively as a model protein for fundamental researches on chromatographic techniques.…”
Section: Introductionmentioning
confidence: 99%